Cultivable marine bacterial isolates from a sponge Hyattella cribriformis - C., Prasanna Kumar; John, Akbar; Khan, Ajmal; Lyla, Nair; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal (Asian Network for Scientific Information, 2013)
Cultivable marine bacteria associated with the sponge Hyattella cribriformis (Hyatt, 1877) was studied through 16S rRNA gene sequencing. These marine bacterial colonies produced on Zobell Marine agar plates were distinguished based on phenotypic characters viz., colony morphology and pigmentations of the individual colonies. The extracted DNA from the individual bacterial isolates was PCR amplified using universal 16S primers and subjected to DNA sequencing. BLAST (Basic Local Alignment Tool) analysis finds that Vibrio diazotrophicus, Bacillus subtilis, B. firmus, Thalassomonas agarivorans, Oleiphilus messinensis, Planococcus maritimus and Brevundimonas vesicularis are the culturable marine bacteria associated with the sponge Hyattella cribriformis. The phylogram constructed clearly delineated the bacterial isolates into its corresponding phylum. The cultivable bacterial density of Hyattella cribriformis was found to be 65x10-5 CFU mL-1. Submitted sequences in NCBI were assigned with accession numbers (FJ834327, FJ834328, FJ834329, FJ845392, FJ845393, FJ845394 and FJ845395). It could be concluded that, application of 16S rRNA sequencing approach would yield novel insights into the diversity of bacteria associated with sponges and hence would help in exploring the commercial importance and their industrial applications.